Composite sponge dressing with wound nursing and state monitoring functions

By using the combined technology of composite sponge structure and BTB dye in wound dressing, the problem of single function and insufficient detection accuracy of existing dressings is solved, real-time monitoring of wound state and efficient pH detection are achieved.

CN119701052APending Publication Date: 2025-03-28IMEIK TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311259667.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing wound dressing has a single function and cannot achieve wound condition monitoring. The accuracy of highly absorbent dressings is affected in the wound exudate pH detection.

Method used

A composite sponge dressing with wound care and condition monitoring functions is adopted. It uses premixed gelatin with PEI and freeze-dried to form a sponge, and then solid phase crosslinking is performed in poor solvents, combined with impregnation treatment of BTB dye, to achieve the function of rapid absorption of leachate and real-time monitoring of wound state.

Benefits of technology

It realizes the rapid absorption of leachate on the wound and reflects the wound state in real time through color changes, warning of bacterial infection and chronic risks in advance, and improves the sensitivity and safety of pH detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701052A_ABST
    Figure CN119701052A_ABST
Patent Text Reader

Abstract

The invention discloses a composite sponge dressing with wound nursing and state monitoring functions. The preparation method comprises the following steps: (1) preparing the non-crosslinked gelatin composite sponge; (2) crosslinking of the composite sponge; and (3) carrying out dye dipping, immersion cleaning and freeze-drying on the cross-linked composite sponge. The prepared composite sponge dressing can quickly absorb wound exudate, can indicate the pH value of the exudate in real time through color change, and can be used for monitoring the wound healing process and early warning bacterial infection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials, and in particular to a composite sponge dressing with both wound care and status monitoring functions. Background Art

[0002] The wound microenvironment plays an important role in the wound healing process. Timely understanding of the changes in the wound microenvironment can accurately intervene in the wound. As one of the main microenvironment-related factors, changes in wound pH often reflect important information. It is reported (Proc. Natl Acad. Sci., 2011, 108, 2432-2437) that the wound pH will change with the development of the wound. Monitoring the wound pH can track the healing progress of the wound; in addition, an increase in wound pH may indicate the occurrence of bacterial infection (Ther. Deliv., 2019, 10, 719-735; Sensors 2019, 19, 991). Monitoring the wound pH can understand the bacterial infection of the wound, so that corresponding treatment can be given in time.

[0003] In clinical practice, the detection of wound pH is mainly carried out with the help of pH test paper. On the one hand, this detection method is prone to dye shedding and dye entering the wound; on the other hand, the wound usually needs to be treated with dressings, and the dressing needs to be uncovered during detection, which is easy to cause secondary damage to the wound. Therefore, the development of an integrated diagnosis and treatment dressing with wound pH detection function can solve these problems. Patent CN209847577U discloses an automatic detection dressing that can understand the healing of the wound by monitoring the pH of the wound. However, the dressing uses pH test paper as a detection layer, has a complex multi-layer structure, and has a cumbersome preparation process. Patent US20200069482A1 discloses a pH indicator dressing that can monitor wounds and wound infections. It uses alginate and pH indicator dye to prepare microspheres, and then the microspheres are compounded with a gel matrix to make a dressing; or thermoplastic polyurethane is mixed with pH indicator dyes, and then spun into nanofiber mats. The color change of the dressing can indicate the presence of wound infection or chronic trauma status, and can be used to detect abnormal healing of acute, chronic or burn wounds at an early stage. Patent CN116370699A discloses a mechanically enhanced hydrogel wound dressing, which uses an aldehyde-modified polysaccharide polymer as a substrate, and successively introduces gelatin, branched polyethyleneimine (PEI) or carboxymethyl chitosan and other amino-containing polymers and pH color-changing materials, antibacterial drugs, and mechanical reinforcement materials, and then cross-links into gels through Schiff base reactions at room temperature. The gel dressing can monitor the pH changes of the wound through color changes and has the function of releasing drugs in response to pH, has antibacterial properties and excellent mechanical properties. However, the PEI of the dressing is cross-linked with the polysaccharide polymer substrate by Schiff base bonds, which has the defects of easy degradation and unstable structure of the gel dressing. In addition, none of the above-mentioned patents has studied the water absorption performance of the dressing, and high water absorption is a prerequisite for the dressing to be used for pH detection of wound exudate. In particular, most dressings are mainly hydrogels, and the large amount of water contained in them will seriously dilute the wound exudate, thereby affecting the accuracy of pH detection.

[0004] Sponge is a porous material with high water absorption. Sponge dressings made of biocompatible materials are widely used for wound care. CN113227255A discloses the use of gelatin and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide, N-hydroxysuccinimide and their mixtures as cross-linking agents to carry out cross-linking reaction to obtain gelatin sponge as a wound auxiliary material, but it is difficult to monitor the wound healing in real time. The present invention provides a composite sponge dressing with both wound care and status monitoring functions. The dressing can quickly absorb a large amount of exudate, and can also indicate the wound status in real time through color changes, thereby providing early warning of bacterial infection and chronicity risks of the wound. Summary of the invention

[0005] In view of the problem that current wound dressings have a single function and cannot realize wound status monitoring, a composite sponge dressing with both wound care and status monitoring functions and a preparation method thereof are provided, which can quickly absorb exudate and timely reflect the wound status through color changes.

[0006] In order to achieve the above object, the present invention provides a method for preparing a composite sponge dressing having both wound care and status monitoring functions, which comprises the following steps:

[0007] (1) mixing gelatin and water, adjusting the solution pH to 6.5-9.0, adding polyethyleneimine (PEI), and uniformly dispersing to obtain a mixed solution;

[0008] (2) freeze-drying the mixed solution obtained in step (1) to obtain a non-cross-linked composite sponge;

[0009] (3) adding the non-crosslinked composite sponge obtained in step (2) into a mixed solution of carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) to perform a solid phase crosslinking reaction to obtain a crosslinked composite sponge;

[0010] (4) After washing the cross-linked composite sponge obtained in step (3), adding it into a bromothymol blue (BTB) solution, immersing it, and freeze-drying it to obtain a composite sponge dressing.

[0011] Furthermore, the concentration of the gelatin in step (1) is 1 to 50 mg / mL (such as 1 mg / mL, 2 mg / mL, 5 mg / mL, 10 mg / mL, 20 mg / mL, 50 mg / mL), preferably 5 to 20 mg / mL.

[0012] In one embodiment of the present invention, the concentration of gelatin in step (1) is 10 mg / mL.

[0013] In one embodiment of the present invention, the concentration of gelatin in step (1) is 20 mg / mL.

[0014] Furthermore, in step (1), the mass ratio of gelatin to PEI is 2 to 50:1 (such as 2:1, 3:1, 5:1, 10:1, 15:1, 20:1, 50:1), preferably, 10 to 20:1.

[0015] In one embodiment of the present invention, the mass ratio of gelatin to PEI in step (1) is 20:1.

[0016] In one embodiment of the present invention, the mass ratio of gelatin to PEI in step (1) is 10:1.

[0017] Further, the average molecular weight of the PEI in step (1) is 5000-20000 Da (such as 5000 Da, 5500 Da, 6000 Da, 6500 Da, 7000 Da, 7500 Da, 8000 Da, 8500 Da, 9000 Da, 9500 Da, 9600 Da, 9700 Da, 9800 Da, 9900 Da, 10000 Da, 11000 Da, 12000 Da, 13000 Da, 14000 Da, 15000 Da, 20000 Da), preferably 8000-15000 Da, and more preferably 10000 Da.

[0018] Furthermore, the mixing temperature in step (1) is 0 to 100°C (such as 0°C, 10°C, 20°C, 30°C, 40°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C), preferably 50 to 90°C.

[0019] In one embodiment of the present invention, the mixing temperature in step (1) is 80°C.

[0020] Furthermore, the mixing time in step (1) is 5 to 60 min (such as 5 min, 10 min, 20 min, 30 min, 60 min), preferably 20 to 40 min.

[0021] In one embodiment of the present invention, the mixing time in step (1) is 30 minutes.

[0022] Furthermore, the step (1) of adjusting the solution pH comprises the following steps: adjusting the pH to 6.5 to 9.0 (such as 6.5, 7.0, 7.2, 7.5, 8.0, 9.0) with an alkaline solution.

[0023] Furthermore, the alkaline solution is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate or triethylamine. Preferably, the alkaline solution is sodium hydroxide.

[0024] In one embodiment of the present invention, the step (1) of adjusting the solution pH comprises the following steps: adjusting the pH to 7.2 with a sodium hydroxide solution.

[0025] Furthermore, the mass concentration of the sodium hydroxide solution is 0.5-2% (such as 0.5%, 0.6%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%), preferably, 0.5-1.5%.

[0026] In one embodiment of the present invention, the mass concentration of the sodium hydroxide solution is 1%.

[0027] Furthermore, the solvent of the mixed solution in step (3) is selected from one of ethanol, methanol and isopropanol, preferably ethanol.

[0028] Furthermore, the temperature of the cross-linking reaction in step (3) is 0-50°C (such as 0°C, 5°C, 10°C, 15°C, 20°C, 21°C, 23°C, 25°C, 27°C, 30°C, 32°C, 35°C, 37°C, 40°C, 45°C, 50°C), preferably 25°C.

[0029] In one embodiment of the present invention, the reaction in step (3) is a shaking cross-linking reaction at 25°C.

[0030] Furthermore, the reaction time of step (3) is 3 to 60 h (such as 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 35 h, 40 h, 45 h, 46 h, 47 h, 48 h, 49 h, 50 h, 55 h, 60 h), preferably 5 to 50 h, and more preferably 6 to 48 h.

[0031] In one embodiment of the present invention, the reaction time of step (3) is 6 hours.

[0032] In one embodiment of the present invention, the reaction time of step (3) is 24 hours.

[0033] In one embodiment of the present invention, the reaction time of step (3) is 48 hours.

[0034] Furthermore, in step (3), the mass ratio of EDC·HCl to gelatin is 0.02-0.2:1.

[0035] In one embodiment of the present invention, the mass ratio of EDC·HCl to gelatin is 0.1:1.

[0036] In one embodiment of the present invention, the mass ratio of EDC·HCl to gelatin is 0.05:1.

[0037] In one embodiment of the present invention, the mass ratio of EDC·HCl to gelatin is 0.025:1.

[0038] Further, in step (3), the mass ratio of EDC·HCl to NHS is 0.5-5:1 (e.g., 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 3.0:1, 3.5:1, 4.0:1, 4.5:1, 5.0:1), preferably 1-3:1, and more preferably 1-2.5:1.

[0039] In one embodiment of the present invention, the mass ratio of EDC·HCl to NHS in step (3) is 1.67:1.

[0040] In one embodiment of the present invention, the mass ratio of EDC·HCl to NHS in step (3) is 2:1.

[0041] In one embodiment of the present invention, step (3) comprises: preparing an ethanol solution containing EDC·HCl and NHS, immersing the non-crosslinked composite sponge obtained in step (2) in the solution, performing a solid phase crosslinking reaction, and obtaining a crosslinked composite sponge.

[0042] In the preparation of the existing composite sponge, PEI is usually added when the sponge is cross-linked to achieve the cross-linking of the sponge and the modification of PEI at the same time. At this time, since the sponge has been formed, the PEI will be unevenly distributed in the sponge, and the cross-linking effect is poor. However, the present invention mixes PEI and gelatin in an aqueous solution in advance, obtains a sponge through freeze drying, and then performs solid phase cross-linking in a poor solvent, so that the PEI and gelatin after freeze drying are closely combined as the skeleton of the sponge, ensuring the uniformity of the distribution of PEI in the sponge matrix, which is more conducive to the cross-linking reaction and improves the cross-linking efficiency.

[0043] In addition, it is known in the art that in the face of low-concentration gelatin solutions, there is a problem of difficulty in completing crosslinking in a solution state. This is because at low concentrations, the collision probability between the active NHS ester formed by the reaction and the gelatin amino group is very low, the crosslinking efficiency is greatly reduced, and the active NHS ester half-life is short, and it fails before the crosslinking is completed, which makes it difficult for the crosslinking reaction to occur. Limited by the limited number of carboxyl and amino groups in the low-concentration gelatin solution, even if the amount of EDC·HCl and NHS is greatly increased, the improvement in the degree of crosslinking is also limited, and it may also bring about the problem of difficulty in removing impurities. Based on this, the present invention adopts a process of first freeze-drying gelatin to form a sponge, and then performing solid-phase crosslinking in a poor solvent such as ethanol, which can smoothly achieve crosslinking, and can obtain a composite sponge dressing with low apparent density and high water absorption, which has a good clinical use effect.

[0044] Furthermore, the solvent of the BTB solution in step (4) is selected from one of ethanol, methanol, isopropanol and alkaline aqueous solution, preferably ethanol.

[0045] Furthermore, in step (4), the mass ratio of BTB to gelatin is 0.002 to 0.1:1.

[0046] In one embodiment of the present invention, the mass ratio of BTB to gelatin in step (4) is 0.002:1.

[0047] In one embodiment of the present invention, the mass ratio of BTB to gelatin in step (4) is 0.02:1.

[0048] In one embodiment of the present invention, the mass ratio of BTB to gelatin in step (4) is 0.1:1.

[0049] Furthermore, the immersion treatment time in step (4) is 0.2 to 2 h (such as 0.2 h, 0.3 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.2 h, 1.5 h, 2 h), preferably 0.2 to 1.5 h.

[0050] In one embodiment of the present invention, the immersion treatment time in step (4) is 0.5 h.

[0051] In one embodiment of the present invention, the immersion treatment time in step (4) is 1 hour.

[0052] The inventors have found through a large number of experiments that there is a stronger binding force between the composite sponge and BTB molecules than other substrates such as filter paper. This is firstly because the gelatin in the sponge is a protein, rich in amino acids such as hydroxyproline and methionine, which have a large number of polar groups such as carboxyl, amino, hydroxyl, and amide bonds, which can form a large number of hydrogen bonds and ionic bonds with polar BTB molecules; secondly, the PEI in the composite sponge is a typical cationic polymer, which can be firmly bound to the negatively charged BTB through electrostatic interaction; finally, the three-dimensional porous structure of the composite sponge provides a large number of binding sites for BTB molecules, thereby achieving efficient loading of BTB and avoiding the common problems of poor binding and easy leakage of BTB and sponge substrates.

[0053] In addition, compared with the process of simultaneously carrying out the cross-linking reaction and the BTB impregnation, the present invention avoids the problem that when BTB and the cross-linking agent are added at the same time, BTB is easily involved in the cross-linking reaction and affects the detection performance by impregnating the BTB dye after the sponge is cross-linked. The composite sponge dressing prepared by the process of the present invention has a strong binding force between the sponge substrate and the BTB dye through static electricity, hydrogen bonding, ionic interaction, etc., has a good loading effect, avoids dye leakage during use of the dressing, and has a higher pH detection sensitivity.

[0054] In a second aspect, the present invention provides a composite sponge dressing prepared by the aforementioned preparation method.

[0055] In a third aspect, the present invention provides an application of the composite sponge dressing prepared by the aforementioned preparation method in the preparation of tissue engineering materials, medicines, and cosmetics;

[0056] Preferably, the tissue engineering material is a biomaterial implant or a coating thereof;

[0057] The drug is a medical dressing, a wound healing material or a clinical pH monitoring material;

[0058] The cosmetic is a cosmetic dressing or a skin pH monitoring material.

[0059] The present invention has achieved the following technical effects:

[0060] 1. The composite sponge is obtained by premixing PEI and gelatin solution, freeze-drying to form a sponge, and then solid-phase crosslinking in a poor solvent. The solution premixing ensures the uniform dispersion of PEI and gelatin. After freeze drying, PEI and gelatin are closely combined as the skeleton of the sponge, which is conducive to the subsequent crosslinking reaction, improves the crosslinking efficiency, and solves the problem that gelatin, PEI and crosslinking agent cannot be crosslinked in solution at the same concentration.

[0061] 2. By impregnating the sponge with BTB dye after the sponge is cross-linked, the problem of BTB and the cross-linking agent being easily involved in the cross-linking reaction and affecting the detection performance when added at the same time is avoided, ensuring that the prepared sponge dressing has high pH detection sensitivity.

[0062] 3. By utilizing the electrostatic, hydrogen and ionic bonds between the dye molecules and the dressing substrate, efficient BTB loading is achieved, avoiding dye leakage during the use of the dressing and ensuring the safety of the dressing.

[0063] 4. The composite sponge dressing prepared by the present invention has excellent water absorption performance, can quickly absorb a large amount of wound exudate, and the water absorption performance can reach more than 35 times, and can present different colors according to the different pH values ​​of the exudate, so as to monitor the wound state in real time. In addition, the raw materials of the composite sponge dressing are widely available, the cost is low, it is green and environmentally friendly, the preparation method is simple and easy, and the product performance is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 Photos of composite sponge dressings (a-C1, b-B1, c-B4).

[0065] Figure 2 These are photos of the composite sponge dressing B1 obtained in Example 6 after absorbing different pH buffer solutions.

[0066] Figure 3 These are photos of the composite sponge dressing C2 obtained in Comparative Example 2 after absorbing different pH buffer solutions.

[0067] Figure 4 These are photos of the BTB test paper C4 obtained in Comparative Example 4 after absorbing different pH buffer solutions.

[0068] Figure 5 These are photos of the composite sponge dressing B1 obtained in Example 6 after absorbing different pH buffer solutions (containing 10% fetal bovine serum).

[0069] Figure 6 The photographs are of dye leakage during the simulated exudate pH detection process using the composite sponge dressing B1 in Example 6 and a commercially available broad pH test paper. DETAILED DESCRIPTION

[0070] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0071]

[00136] Various publications, patents, and published patent specifications are cited herein, the disclosures of which are incorporated by reference in their entireties.

[0072] The raw materials and reagents used in this article can be obtained commercially.

[0073] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Example 1 Preparation of carrier composite sponge A1

[0075] Weigh 0.5g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0076] Prepare 100 mL of ethanol solution containing 25 mg / mL LEDC·HCl and 15 mg / mL NHS, and soak the non-crosslinked sponge in the solution for 24 hours for crosslinking. After the crosslinking is completed, take out the sponge and wash it with 500 mL of purified water for 1 hour × 3 times to obtain carrier composite sponge A1.

[0077] Example 2 Preparation of carrier composite sponge A2

[0078] Weigh 0.5g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 50mg PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0079] Prepare 100 mL of ethanol solution containing 25 mg / mL LEDC·HCl and 15 mg / mL NHS, and soak the non-crosslinked sponge in the solution for 24 hours for crosslinking. After the crosslinking is completed, take out the sponge and wash it with 500 mL of purified water for 1 hour × 3 times to obtain a carrier composite sponge A2.

[0080] Example 3 Preparation of carrier composite sponge A3

[0081] Weigh 1g of gelatin and add it to 50mL of water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg of PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0082] Prepare 100 mL of ethanol solution containing 25 mg / mL LEDC·HCl and 15 mg / mL NHS, and soak the non-crosslinked sponge in the solution for 24 hours for crosslinking. After the crosslinking is completed, take out the sponge and wash it with 500 mL of purified water for 1 hour × 3 times to obtain a carrier composite sponge A3.

[0083] Example 4 Preparation of carrier composite sponge A4

[0084] Weigh 0.5g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0085] Prepare 100 mL of ethanol solution containing 50 mg / mL LEDC·HCl and 30 mg / mL NHS, and soak the non-crosslinked sponge in the solution for 6 hours for crosslinking. After the crosslinking is completed, take out the sponge and wash it with 500 mL of purified water for 1 hour × 3 times to obtain carrier composite sponge A4.

[0086] Example 5 Preparation of carrier composite sponge A5

[0087] Weigh 0.25g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0088] 100 mL of ethanol solution containing 10 mg / mL LEDC·HCl and 5 mg / mL NHS was prepared, and the non-crosslinked sponge was immersed in the solution for 48 hours for crosslinking. After the crosslinking was completed, the sponge was taken out and washed with 500 mL of purified water for 1 hour × 3 times to obtain a carrier composite sponge A5.

[0089] Example 6 Preparation of composite sponge dressing B1

[0090] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the carrier composite sponge A1 was immersed in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B1 ( Figure 1 ).

[0091] Example 7 Preparation of composite sponge dressing B2

[0092] 50 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.5 mg / mL BTB impregnation solution, and then the carrier composite sponge A1 was immersed in the impregnation solution for 15 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B2.

[0093] Example 8 Preparation of composite sponge dressing B3

[0094] 1 mg of BTB was weighed and dissolved in 100 mL of methanol to obtain a 0.01 mg / mL BTB impregnation solution, and then the carrier composite sponge A1 was immersed in the impregnation solution for 1 hour for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed 3 times with purified water, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The saturated sponge was then freeze-dried to obtain a color-changing composite sponge dressing B3.

[0095] Example 9 Preparation of composite sponge dressing B4

[0096] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the carrier composite sponge A2 was immersed in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B4 ( Figure 1 ).

[0097] Example 10 Preparation of composite sponge dressing B5

[0098] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the carrier composite sponge A3 was immersed in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B5.

[0099] Example 11 Preparation of composite sponge dressing B6

[0100] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the carrier composite sponge A4 was immersed in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B6.

[0101] Example 12 Preparation of composite sponge dressing B7

[0102] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the carrier composite sponge A5 was immersed in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The water-absorbed sponge was then freeze-dried to obtain a color-changing composite sponge dressing B7.

[0103] Comparative Example 1: Preparation of PEI-free sponge dressing C1

[0104] Weigh 0.5 mg of gelatin and add it to 50 mL of water, stir at 80°C for 30 min to completely dissolve the gelatin, cool to room temperature, and adjust the pH to 7.2 with 1% NaOH solution. Freeze-dry the solution to obtain a non-cross-linked sponge.

[0105] Prepare 100 mL of ethanol solution containing 25 mg / mL LEDC·HCl and 15 mg / mL NHS, and soak the non-crosslinked sponge in the solution for 24 hours for crosslinking. After crosslinking, take out the sponge and wash it with 500 mL of purified water for 3 times with shaking, 1 hour each time.

[0106] 10 mg of BTB was weighed and dissolved in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then the cross-linked sponge was immersed in the impregnation solution for 30 min for impregnation treatment. After the impregnation was completed, the sponge was shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The saturated sponge was then freeze-dried to obtain sponge dressing C1.

[0107] Comparative Example 2: Preparation of composite sponge dressing C2 by simultaneous crosslinking and BTB impregnation

[0108] Weigh 0.5g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg PEI and add it to the gelatin solution and stir evenly. Freeze-dry the mixture to obtain a non-cross-linked composite sponge.

[0109] Prepare 100 mL of ethanol solution containing 25 mg / mL EDC·HCl, 15 mg / mL NHS, and 0.1 mg / mL BTB, and soak the non-crosslinked sponge in the solution for 24 hours for crosslinking and impregnation. After crosslinking, take out the sponge and shake and soak the sponge 3 times, each time for 1 hour, to remove impurities such as free BTB molecules, EDC·HCl, and NHS that were not successfully loaded. Then freeze-dry the saturated sponge to obtain sponge dressing C2.

[0110] Comparative Example 3: Preparation of carrier composite sponge C3 by solution crosslinking method

[0111] Weigh 0.5g gelatin and add it to 50mL water. Stir at 80℃ for 30min to completely dissolve the gelatin. After cooling to room temperature, adjust the pH to 7.2 with 1% NaOH solution. Weigh 25mg PEI and add it to the gelatin solution and stir evenly. Add 1.25g EDC·HCl and 0.75g NHS to the solution, stir evenly and let stand at 25℃ for 24h for crosslinking. Then freeze-dry to obtain carrier composite sponge C3.

[0112] The results showed that gel could not be formed by solution cross-linking, and the composite sponge C3 obtained after freeze-drying quickly dissolved in water. This was because the mixed solution of gelatin and PEI could not achieve cross-linking in the solution state at the concentration, so it quickly dissolved when placed in water. This was because the extremely dilute concentration made the collision probability between the active NHS ester formed in the reaction and the amino group very low, and the cross-linking efficiency was greatly reduced. At the same time, the active NHS ester had a short half-life and became ineffective before the cross-linking was completed, thus resulting in cross-linking failure.

[0113] Comparative Example 4: Preparation of BTB Test Paper C4

[0114] Weigh 10 mg of BTB and dissolve it in 100 mL of ethanol to obtain a 0.1 mg / mL BTB impregnation solution, and then immerse the filter paper in the impregnation solution for 30 minutes for impregnation treatment. After the impregnation is completed, the filter paper is shaken and washed with purified water for 3 times, each time for 1 hour, to remove the free BTB molecules that were not successfully loaded. The filter paper is then freeze-dried to obtain BTB test paper C4. It was found that the obtained BTB test paper C4 and the filter paper before impregnation were both white, indicating that BTB is difficult to load onto the filter paper under this process condition.

[0115] Performance Test:

[0116] Appearance of composite sponge dressing

[0117] The appearance of the composite sponge dressing samples of Example 6, Example 9 and Comparative Example 1 was directly observed, and their morphology was as follows: Figure 1 As shown. Figure 1 It can be seen that the color of the composite sponge dressing B1 of Example 6 is darker, indicating that the sponge is loaded with more BTB dye molecules. Compared with the composite sponge dressing B1, the color of the composite sponge dressing C1 obtained under the same BTB impregnation conditions in Comparative Example 1 is significantly lighter, indicating that its loading effect on BTB is poor. This is mainly due to the lack of electrostatic interaction between BTB and the sponge in Comparative Example 1 due to the lack of PEI. As the amount of PEI used increases, the color of the composite sponge dressing B4 of Example 9 also deepens further, indicating that the positively charged PEI gives the composite sponge and BTB a stronger binding force.

[0118] Water absorption performance test of composite sponge dressing

[0119] The composite sponge dressing samples of Examples 6 to 12 and Comparative Example 1 were cut into small pieces of about 10 mg, and their dry weights were weighed and recorded as m1. Then, they were immersed in water for 10 seconds, and their weights after immersion were measured and recorded as m2. The water absorption rate was calculated according to the following formula:

[0120]

[0121] The water absorption rates of the composite sponge dressing samples are shown in Table 1. It can be seen from Table 1 that the water absorption rates of composite sponge dressings B1-B6 are high, all above 35 times, and the water absorption rate of composite sponge dressing B7 is as high as 44.6, indicating that the composite sponge dressings prepared by this process have high water absorption. In addition, the water absorption rate of comparative example C1 is 37.1, which is much lower than B1, indicating that in sponge dressing B1, the excellent hydrophilic property of PEI enhances the water absorption of the sponge.

[0122] Table 1. Water absorption rate of composite sponge dressing samples obtained by different processes

[0123] sample Water absorption rate B1 42.1 B2 43.9 B3 40.3 B4 42.7 B5 35.6 B6 39.1 B7 44.6 C1 37.1

[0124] pH responsiveness test of composite sponge dressing

[0125] The composite sponge dressing samples of Example 6 and Comparative Example 2 were cut into 6 small pieces of 0.6 cm×1.0 cm×0.2 cm, immersed in 0.1 M PBS with pH values ​​of 5.9, 6.4, 6.8, 7.2, 7.7 and 8.0 for 30 s respectively, and then taken out and compared to observe the color differences of the composite sponge dressings.

[0126] The composite sponge dressing sample of Example 6 was cut into 6 small pieces of 0.6 cm×1.0 cm×0.2 cm, and immersed in 0.1 M PBS containing 10% (v / v) fetal bovine serum at pH 5.9, 6.4, 6.8, 7.2, 7.7 and 8.0 for 30 s, respectively. Then the color differences of the composite sponge dressings were taken out and compared.

[0127] like Figure 2 As shown, when testing PBS solutions with different pH values, the composite sponge dressing B1 appears bright yellow, light yellow, yellow-green, green, sky blue and dark blue at pH 5.9, 6.4, 6.8, 7.2, 7.7 and 8.0, respectively, with obvious color recognition, so the pH value of the solution can be accurately judged according to the color.

[0128] like Figure 3As shown, under the same test conditions, the composite sponge dressing C2 can only achieve a change from light yellow to light green in the same pH detection range, wherein the pH changes from 5.9 to 6.4, and then to 6.8, and the color of the composite sponge dressing has almost no significant change, all showing yellow, and it is difficult to reflect the change in pH, indicating that its pH detection sensitivity is insufficient, which may be due to the fact that when preparing the C2 composite sponge dressing, the BTB dye is added together with the cross-linking agent, and the sulfonic acid group and hydroxyl group of BTB participate in the cross-linking reaction, thereby causing the pH response ability of the loaded BTB to decrease, and the detection sensitivity is poor. It is further confirmed that the use of the present invention, which is to carry out the impregnation loading process of the BTB dye after the sponge is cross-linked, can improve the loading effect while also having a higher pH response effect, and can better meet the needs of clinical use.

[0129] like Figure 4 As shown, under the same test conditions, BTB test paper C4 is white in buffers of different pH values ​​and has no pH responsiveness, indicating that the filter paper cannot load BTB dye after the same impregnation process as the composite sponge. This is because the filter paper is mainly composed of cellulose with a simple structure, while the composite sponge is composed of positively charged PEI and proteins rich in amino acids such as hydroxyproline and methionine, which can be tightly combined with polar, negatively charged BTB molecules by hydrogen bonds, ionic bonds and electrostatic effects. This result fully illustrates that, relative to the test paper, the composite sponge prepared by the present invention is more suitable for loading BTB dye for detection.

[0130] like Figure 5 As shown, when detecting PBS solutions containing fetal bovine serum at different pH values, the composite sponge dressing B1 showed bright yellow, light yellow, yellow-green, green, sky blue and dark blue at pH 5.9, 6.4, 6.8, 7.2, 7.7 and 8.0, respectively. The color change trend was consistent with the result of detecting PBS without fetal bovine serum, and it also had obvious color recognition, indicating that the introduction of fetal bovine serum did not significantly affect the pH responsiveness of the composite sponge, further illustrating that the composite sponge dressing of the present invention also has high sensitivity and responsiveness in clinical use.

[0131] Composite sponge dressing and pH test paper simulate the detection process of dye leakage test

[0132] The composite sponge dressing of Example 6 and the commercially available broad pH test paper were cut into small pieces of 1.0 cm×0.6 cm, and then 200 μL of PBS (0.1 M, pH=8) was dripped onto a 1.5×1.0 cm absorbent cotton sheet, and the composite sponge dressing B1 and the broad pH test paper were placed on the absorbent cotton sheet with PBS, and gently pressed to make the pH test paper and the absorbent cotton sheet saturated with the exudate, and then left to stand for 5 minutes. Then the composite sponge dressing and the test paper were removed, and the leakage of the dye on the absorbent cotton sheet was observed.

[0133] like Figure 6 As shown in the figure, after the pH test paper was removed, a large amount of dye remained on the upper layer of the absorbent cotton, while after the composite sponge dressing B1 was removed, no dye was found on the upper layer of the absorbent cotton, indicating that the BTB dye carried by B1 did not leak. This shows that there is a strong binding force between the BTB dye and the composite sponge dressing substrate, and BTB is not easy to fall off. Therefore, the prepared composite sponge dressing can be safely used for wound care and status monitoring.

[0134] The same method was used to test the dye leakage of composite sponges B2, B3, B4, B5, B6 and B7, and the results showed that no obvious dye leakage was found.

Claims

1. A method for preparing a composite sponge dressing having both wound care and status monitoring functions, comprising the following steps: (1) mixing gelatin and water, adjusting the pH of the solution to 6.5-9.0, and adding polyethyleneimine (PEI) to obtain a mixed solution; (2) freeze-drying the mixed solution obtained in step (1) to obtain a non-cross-linked composite sponge; (3) adding the non-crosslinked composite sponge obtained in step (2) into a mixed solution of carbodiimide hydrochloride (EDC·HCl) and N-hydroxysuccinimide (NHS) to perform a solid phase crosslinking reaction to obtain a crosslinked composite sponge; (4) After washing the cross-linked composite sponge obtained in step (3), adding it into a bromothymol blue (BTB) solution, immersing it, and freeze-drying it to obtain a composite sponge dressing.

2. The preparation method according to claim 1, characterized in that The concentration of gelatin in step (1) is 1 to 50 mg / mL, preferably 5 to 20 mg / mL.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the mass ratio of gelatin to PEI is 2 to 50:1, preferably 10 to 20:1; Preferably, the average molecular weight of the PEI in step (1) is 5000-20000 Da, preferably 8000-15000 Da.

4. The preparation method according to claim 1 or 2, characterized in that: The step (1) of adjusting the solution pH comprises the following steps: adjusting the pH to 6.5-9.0 with an alkaline solution, wherein the alkaline solution is selected from one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate or triethylamine; preferably, the alkaline solution is sodium hydroxide.

5. The preparation method according to claim 1 or 2, characterized in that: The temperature of the cross-linking reaction in step (3) is 0 to 50° C. and the time is 3 to 60 hours.

6. The preparation method according to claim 1 or 2, characterized in that: In step (3), the mass ratio of EDC·HCl to gelatin is 0.02-0.2:

1.

7. The preparation method according to claim 1 or 2, characterized in that: In step (3), the mass ratio of EDC·HCl to NHS is 0.5 to 5:1, preferably 1 to 3:1, and more preferably 1 to 2.5:

1.

8. The preparation method according to claim 5, characterized in that: In step (4), the mass ratio of BTB to gelatin is 0.002-0.1:

1.

9. The composite sponge dressing prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the composite sponge dressing prepared by the preparation method according to any one of claims 1 to 8 or the composite sponge dressing according to claim 9 in the preparation of tissue engineering materials, medicines and cosmetics; Preferably, the tissue engineering material is a biomaterial implant or a coating thereof; The drug is a medical dressing, a wound healing material or a clinical pH monitoring material; The cosmetic is a cosmetic dressing or a skin pH monitoring material.

Citation Information

Patent Citations

  • Foam compositions, foam matrices and methods

    CN113227255A

  • Mechanical enhanced hydrogel wound dressing and preparation method thereof

    CN116370699A

  • Automatic detection dressing

    CN209847577U

  • pH Indicator Dressing for Monitoring of Wound and Infection

    US20200069482A1